Prediction of F3 populations based on unbalanced diallel crossing systems - Júnior, Antonio Oliveira; Miranda, Glauco Vieira; Cruz, Cosme Damião (Pesquisa Agropecuaria Brasileira, 1999)
The objective of this paper was to predict the properties of F3 generation of the dry bean based on F1 generation data from diallel crosses. Eight hybrid combinations from compatible crosses between seven parents (Diacol Andino, Ica Lhanogrande, Ica Tundama, Rojo 70, Rio Tibagi, Carioca, and Roxo) were analyzed by comparing the unbalance circulating and partial diallel crossing systems. The F1 hybrid combinations and the parents were arranged in a complete randomized design with varying number of replications per treatment under greenhouse conditions. The F3 generation was grown in two areas under field conditions in a complete randomized block design. The following traits, number of pods per plant and seed weight per plant, were evaluated. Prediction based upon general capacity of combination (CGC) in F1 generation was more efficient than performance in F1 generation to predict F3 segregant hybrid combinations. Negative correlation between the generations observed and the predicted generations was noted when the unbalanced circulating diallel crossing systems were used.
Keywords: dry bean; general combing ability; hybrids